A thematic review on successor development in Chinese family business - Meng, Meng; Abdul Wahat, Nor Wahiza; Abdullah, Haslinda; Zairul, Mohd (Human Resource Management Academic Research Society, 2023)
With the research on succession issues in Chinese family businesses, successor factors have been constantly mentioned, but early research on successors in Chinese family businesses was limited. Therefore, the purpose of this study is to focus on successors and conduct a thematic review and analysis of research on succession in Chinese family businesses, and to explore how to correctly identify, train and prepare successors in family businesses. Data for this study were collected through thematic review analysis of 25 publications from 2014 to 2023 using ATLAS.ti 8 as a tool. The analysis revealed five central themes. The results show that founders usually choose their own children to succeed; in addition to subjective consciousness, the founder's decision-making is also affected by the system, environment, culture, etc.; the development of successors should consider aspects such as innovation ability, academic qualifications, experience, and social relationships. This review will provide new insights into the study of successors in Chinese family businesses.